Microfluidics for nano-drug delivery systems: From fundamentals to industrialization - Huan Zhang; Jie Yang; Rongze Sun; Songren Han; Zhaogang Yang; Lesheng Teng (Acta Pharmaceutica Sinica B, 2023)
In recent years, owing to the miniaturization of the fluidic environment, microfluidic technology offers unique opportunities for the implementation of nano drug delivery systems (NDDSs) production processes. Compared with traditional methods, microfluidics improves the controllability and uniformity of NDDSs. The fast mixing and laminar flow properties achieved in the microchannels can tune the physicochemical properties of NDDSs, including particle size, distribution and morphology, resulting in narrow particle size distribution and high drug-loading capacity. The success of lipid nanoparticles encapsulated mRNA vaccines against coronavirus disease 2019 by microfluidics also confirmed its feasibility for scaling up the preparation of NDDSs via parallelization or numbering-up. In this review, we provide a comprehensive summary of microfluidics-based NDDSs, including the fundamentals of microfluidics, microfluidic synthesis of NDDSs, and their industrialization. The challenges of microfluidics-based NDDSs in the current status and the prospects for future development are also discussed. We believe that this review will provide good guidance for microfluidics-based NDDSs.